Численное исследование трудноразделимых вокальных согласных команд оператора на основе мел-частотных кепстральных коэффициентов - Федоров, Е. Е. (НТУ "ХПИ", 2013)
Numerical research is carried out article difficultly separable vocal consonants of commands of the operator by means of not expanding compact uniformly continuous mapping based on mel-frequency cepstral factors for formation of a vector of real features and transformation of a vector of real features to a vector of the integer features by means of rationing, scaling and arounding off.
Keywords: звуки; сигнал речевой; команды вербальные; отображения непрерывные